1999
DOI: 10.1159/000018687
|View full text |Cite
|
Sign up to set email alerts
|

Left Colon Substitution with His’ Angle following Total Gastrectomy

Abstract: To resolve the disadvantages of jejunal Roux-en-Y reconstruction following total gastrectomy, we attempted the use of left colon substitution with all anastomoses conducted using mechanical stapling devices. A His’ angle was formed to reduce regurgitation esophagitis. About 25 cm of the left colon with the ascending branch of the left colic artery with an adequate blood supply was brought up to the remnant esophagus without tension on the mesentery. The colon graft was interposed between the esophagus and duod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The broad spectrum of reconstruction methods can be subdivided into those excluding the duodenal passage with or without pouch construction, and others restoring the duodenal passage with or without pouch construction [6, 7]. The construction of a gastric pouch provides an increased reservoir capacity, a higher amount of calories ingested by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The broad spectrum of reconstruction methods can be subdivided into those excluding the duodenal passage with or without pouch construction, and others restoring the duodenal passage with or without pouch construction [6, 7]. The construction of a gastric pouch provides an increased reservoir capacity, a higher amount of calories ingested by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of creating a pouch was to increase food ingestion as well as to enable the temperature of ingested food to approach the body temperature so that the contents may be well mixed with orally administered digestive enzymes [16]. For creation of the pouch, there are techniques available using ileocolon [14,15] and transverse colon [13]. The authors adopted the jejunal J pouch technique because it is easy to create.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the surgical technique of Maki et al [4] alkaline esophagitis due to reflux of duodenal juice was reported because LES was removed, though the pyloric sphincter was preserved. In addition, there were cases with reflux symptoms in which the food content that flowed into the interpositioned jejunum flowed back into the esophagus, and cases in which microgastria occurred because of decreased retention due to single jejunal crus, and therefore, many cases have been reported with low QOL [1,8,[12][13][14][15][16]. The authors attempted to preserve LES in addition to the surgical technique of Maki et al [4].…”
Section: Discussionmentioning
confidence: 99%
“…Since direct anastomosis between the esophagus and the remnant stomach resulted in severe reflux esophagitis, jejunal interposition or Roux-en-Y esophagojejunostomy with side-to-end jejunogastrostomy (double-tract method) has been employed. Recently, gastric substitutes with sufficient capacity for food have been made by the interposition of a jejunal pouch [4,5,16] or a short segment of left colon [17]. Although these gastric substitutes are reported to be useful, the procedures are complicated and timeconsuming, and need several stapling devices.…”
Section: Discussionmentioning
confidence: 99%